Enhancing wildlife conservation awareness through visitor experience of Wildlife Conservation Center in Davao City - Plana, Eloisa Marie (2023)
Wildlife is threatened from all sides, facing down illegal wildlife trade, habitat destruction, invasive species, pollution, and clime change. Reducing these threats requires a vital shift in the way people perceive and interact with wildlife. Education and awareness in turn have significant effects on the success of conservation movements. As such, wildlife conservation centers? ultimate goal is to ensure the survival of these species, and to educate people on living sustainably with other species. Understanding the experiences of the visitors in these wildlife conservation centers is fundamental in the enhancement of their awareness on wildlife conservation. This thesis aimed to explore the potential of a positive visitor experience in raising conservation awareness in three wildlife conservation centers in Davao City: Philippine Eagle Center, Davao Crocodile Park and Zoo, and Aboitiz Cleanergy Park: Pawikan Sanctuary. Thirty respondents per study area were invited to participate in the study, all of which are undergraduate college students. Results indicate at least 57% increase in willingness to participate in conservation after the educational visits. The link between the two variables was tested using Pearson?s correlation. It was determined that visitor experience and conservation awareness in these three centers have a correlation of 0.42, 0.44, and 0.49, all of which implicate a medium-strength positive relationship. Furthermore, architectural interventions were produced from the study to improve visitor experience and promote conservation awareness which are categorized into five elements: wildlife interaction, facility and space, mobility, interactive participation, and learning materials.